Rethinking the sociology of stigma. Issue 4 (July 2018) - Tyler, Imogen; Slater, Tom
Stigma is not a self-evident phenomenon but like all concepts has a history. The conceptual understanding of stigma which underpins most sociological research has its roots in the ground-breaking account penned by Erving Goffman in his best-selling book Stigma: Notes on the Management of Spoiled Identity (1963). In the 50 years since its publication, Goffman's account of stigma has proved a productive concept, in terms of furthering research on social stigma and its effects, on widening public understandings of stigma, and in the development of anti-stigma campaigns. However, this introductory article argues that the conceptual understanding of stigma inherited from Goffman, along with the use of micro-sociological and/or psychological research methods in stigma research, often side-lines questions about where stigma is produced, by whom and for what purposes. As Simon Parker and Robert Aggleton argue, what is frequently missing is social and political questions, such as 'how stigma is used by individuals, communities and the state to produce and reproduce social inequality'. This article expands on Parker and Aggleton's critique of the limitations of existing conceptual understandings of stigma, through an examination of the anti-stigma campaign Heads Together. This high-profile campaign launched in 2016 seeks to 'end the stigma around mental health' and is fronted by members of the British Royal Family. By thinking critically with and about this campaign, this article seeks to both delineate the limitations of existing conceptual understandings of stigma and to begin to develop a supplementary account of how stigma functions as a form of power. We argue that in order to grasp the role and function of stigma in society, scholarship must develop a richer and fuller understanding of stigma as a cultural and political economy. The final part of this introduction details the articles to follow, and the contribution they collectively make to the project of rethinking the sociology of stigma. This collection has been specifically motivated by: (1) how reconceptualising stigma might assist in developing better understandings of pressing contemporary problems of social decomposition, inequality and injustice; (2) a concern to decolonise the discipline of sociology by interrogating its major theorists and concepts; and (3) a desire to put class struggle and racism at the centre of understandings of stigma as a classificatory form of power.